Investigation of useful ambient vibration sources for the application of energy harvesting - Ab Rahman, Mohd Fauzi; Kok, Swee Leong (2012)
Abstract— Ambient vibration is one of the popular sources for energy harvesting due to its ubiquitous present in almost everywhere. For the past few years it has attracted many interests in the design and development of vibration based micro generators for low power electronic applications. The aim of this paper is to investigate on useful ambient vibration sources which would have great potential for the application of energy harvesting. Commonly the acceleration level of ambient vibration is low, in the range < 1 g-level. In this study, the vibration sources from industries (machinery), home appliances and moving vehicle are compiled and compared with suitable energy harvesters designed by other researchers. It may serve as a good guideline for the researchers in designing resonant devices such as the vibration based micro-power generators.